Exposure to heavy metal-contaminated sediments disrupts gene expression, lipid profile, and life history traits in the midge Chironomus riparius. (1st January 2020) - Arambourou, Hélène; Llorente, Lola; Moreno-Ocio, Iñigo; Herrero, Óscar; Barata, Carlos; Fuertes, Inmaculada; Delorme, Nicolas; Méndez-Fernández, Leire; Planelló, Rosario
Abstract: Despite the concern about anthropogenic heavy metal accumulation, there remain few multi-level ecotoxicological studies to evaluate their effects in fluvial ecosystems. The toxicity of field-collected sediments exhibiting a gradient of heavy metal contamination (Cd, Pb, and Zn) was assessed in Chironomus riparius . For this purpose, larvae were exposed throughout their entire life cycle to these sediments, and toxic effects were measured at different levels of biological organization, from the molecular (lipidomic analysis and transcriptional profile) to the whole organism response (respiration rate, shape markers, and emergence rate). Alterations in the activity of relevant genes, as well as an increase of storage lipids and decrease in membrane fluidity, were detected in larvae exposed to the most contaminated sediments. Moreover, reduced larval and adult mass, decrease of larval respiration rate, and delayed emergence were observed, along with increased mentum and mandible size in larvae and decreased wing loading in adults. This study points out the deleterious effects of heavy metal exposure at various levels of biological organization and provides some clues regarding the mode of toxic action. This integrative approach provides new insights into the multi-level effects on aquatic insects exposed to heavy metal mixtures in field sediments, providing useful tools for ecological risk assessment in freshwater ecosystems. Graphical abstract: Image 1 Highlights: Harmful effects were detected in Chironomus riparius exposed to mining sediments. Heavy metals altered the transcriptional profile of genes related to hormonal pathways. Biotransformation metabolism, oxidative stress and oxygen transport were affected. Disruptions in lipid profile, respiration rate and life traits were also observed. Mentum and mandible lengths significantly increased under highly polluted sediments.